Research on the Coordinated Development of “Node-Place” in Intercity Railway Station Areas: A Case Study of the Guangdong–Hong Kong–Macao Greater Bay Area, China - Shuaibing Zhang; Zhengdong Huang; Kaixu Zhao (ISPRS International Journal of Geo-Information)
Intercity railways are key transportation infrastructures in the interconnection of urban agglomerations. Their stations are usually distributed based on densely populated and economically active areas, and they also play roles as regional network nodes, intra-city nodes, and functional areas. However, the academic research on the spatial development of station areas is still very limited. In particular, there is no sufficient in-depth discussion about the coordinated development mechanism of the “regional node-place” and “urban node-place” of intercity railways. Based on the case study of Guangdong–Hong Kong–Macao Greater Bay Area in China (GBA), this paper provides an in-depth analysis of the regional node development level, urban node development level, station area development level, comprehensive station area development level, and coordinated development of “regional node-place” and “urban node-place” in the GBA in 2012, 2016, 2020, and 2023 by constructing a node-place model, development index of regional nodes, development level index, and coupling coordination degree model. Findings: (1) From 2012 to 2023, the development of regional nodes, urban nodes, and places of the GBA intercity railway saw a significant improvement, with the proportion of high-value stations increasing by 13.3%, 7%, and 8.8%, respectively. Despite some improvement on the whole, the three still exhibited an unbalanced spatial distribution of “high in the middle-low in the periphery”; (2) The relative gap in development levels between “regional node-place” and “urban node-place” of intercity railways decreased by 0.159 and 0.168, respectively, showing an overall upward trend, but still showing an unbalanced spatial distribution of “high in the middle-low in the periphery”; (3) The development level of regional nodes and urban nodes is lower than that of areas and is dominated by the unbalance place and dependence types, while the unbalance node and balance types account for less; (4) The coordination of the “regional node-place” and “urban node-place” of intercity railways is gradually improved, and the stations with high coordination and high coordination levels accounts for an increased proportion from 4% to 7% and 8%, respectively. However, the coordination remains at a low level on the whole, with most sites still in the low-level coupling and lower-level coupling stages. Some stations in Guangzhou, Shenzhen, Foshan, and Dongguan have witnessed a level leap and are showing a transition towards a medium to high level of coordinated development, with the surrounding areas moving away from low-level coupling and coordination.